Double-Blind, Randomized Study of the Effects of Influenza Vaccination on the Specific Antibody Response and Clinical Course of Patients with Chronic Fatigue Syndrome - Kenna M Sleigh; Donelda G Danforth; Raymond T Hall; Jonathan A Fleming; H Grant Stiver (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine whether influenza immunization is associated with early side effects, a deleterious impact on the illness course and depressed antibody response in patients with chronic fatigue syndrome (CFS).